Exeresis of the sublingual gland for the treatment of plunging ranula (Research, Society and Development, 2023)
Plunging ranulas are pseudocysts that originate in the sublingual salivary gland and extend into the submandibular space and then into deeper cervical spaces. Several approaches have been described in the literature regarding the treatment of plunging ranula, including surgical and non-surgical methods. Due to this bias, the main objective of the present study is to provide arguments based on clinical and scientific evidence that complete intraoral excision of the sublingual gland is the most rational approach for the treatment of plunging ranula. The article was carried out through a systematic literature review, which included scientific articles indexed in databases such as Google Scholar, SciELO and PubMed. The methodological steps dealt with the definition and application of inclusion and exclusion criteria, bibliographic survey according to the mentioned databases and synthesis in writing the review. Of the 145 results obtained initially, the present work had 27 articles for its construction, in which, reports acquired from the selected studies declare that the removal of the sublingual gland is the best choice in the surgical management of the plunging ranula instead of the excision of the cyst, since the gland presents itself as the source of formation of this mucus whose accumulation is related to the pathological process. Thus, this treatment approach depends on the surgeon's experience, through knowledge about the pathological alterations of the salivary glands, their clinical characteristics and the involvement of adjacent structures, taking into account the extent and position of the lesion.